The Effect of Hologram Technology in Reviving the Interior Spaces of Archaeological Buildings: Museums as a Case Study - Azali, Mohammad; Tabbalat, Shereen; Kakani, Anan (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims to explore the impact and role of digital optical technologies, specifically "hologram" technology, within the interior spaces of historical buildings that have been repurposed as museums. It aims to guide designers in implementing this technology, particularly in historical buildings intended to be transformed into heritage museums using hologram technology. This technology helps create virtual images of some deteriorated or damaged interior spaces and envisions the building's original form as it once was. Methods: The study adopts a descriptive approach to analyze various studies, references, and real-life projects that have experimented with hologram technology. The objective is to deduce the impact and significance of using this technology in historical buildings, especially those intended for conversion into museums. Results: The research concludes that the use of hologram technology significantly aids in visualizing the interior spaces and their historical details in a complete manner, compensating for missing or damaged elements. Additionally, it fosters the creation of innovative new forms alongside the tangible reality. This technology has become a favored method for some designers working on such types of buildings. Conclusions: The study highlights the positive impact and role of hologram technology in reviving and enhancing the interior spaces of historical buildings, supported by practical examples from various heritage museums that display lost and highlighted engravings using optical projection. It encourages interior designers to adopt this technology in similar heritage settings.